BoneNET: a network model of bone microstructure and dynamics. (1st January 2013) - Kim, Taehyong; Bone, Lawrence; Ramanathan, Murali; Zhang, Aidong
We develop a network model of bone microstructure and dynamics, BoneNET, which is capable of quantitative assessment of Bone Mineral Density (BMD) and bone remodelling dynamics. First, we introduce a network model of bone microstructure by describing structural properties and process of bone network modelling. Secondly, we explain a mathematical model of bone microstructure by analysing the density for mineralised fibres of bone microstructure. Finally, we provide a bone remodelling dynamics among osteoblast and osteoclast and study bone networks by proposing several measurements to calculate bone strength and identify critical elements in bone microstructure.